2005
DOI: 10.1128/aem.71.12.8284-8291.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Unique Chromosomal Copper Resistance Gene Cluster from X anthomonas campestris pv. vesicatoria

Abstract: We characterized the copper resistance genes in strain XvP26 of Xanthomonas campestris pv. vesicatoria, which was originally isolated from a pepper plant in Taiwan. The copper resistance genes were localized to a 7,652-bp region which, based on pulsed-field gel electrophoresis and Southern hybridization, was determined to be located on the chromosome. These genes hybridized only weakly, as determined by Southern analysis, to other copper resistance genes in Xanthomonas and Pseudomonas strains. We identified fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 47 publications
2
50
0
1
Order By: Relevance
“…vesicatoria, cinA is associated with the multicopper oxidase, a TolC-like outer membrane protein, and a twocomponent heavy metal sensor kinase and response regulator. Basim et al (1) reported that for X. campestris pv. vesicatoria, disruption of cinA (ORF5) resulted in a partial loss of copper resistance, while disruption of the sensor kinase gene (ORF1), a multicopper oxidase gene (ORF4), or the TolC family outer membrane factor gene (ORF3) had a much greater effect.…”
Section: Discussionmentioning
confidence: 99%
“…vesicatoria, cinA is associated with the multicopper oxidase, a TolC-like outer membrane protein, and a twocomponent heavy metal sensor kinase and response regulator. Basim et al (1) reported that for X. campestris pv. vesicatoria, disruption of cinA (ORF5) resulted in a partial loss of copper resistance, while disruption of the sensor kinase gene (ORF1), a multicopper oxidase gene (ORF4), or the TolC family outer membrane factor gene (ORF3) had a much greater effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of genes encoding proteins have been shown to be involved in bacterial resistance to such heavy metals as cobalt, zinc, cadmium, arsenic, copper, molybdenum and silver (Nies, 1995(Nies, , 1999Grunden and Shanmugam, 1997;Rensing et al, 1997Rensing et al, , 1999Brown et al, 2002;Parro and Moreno-Paz, 2003;Zahalak et al, 2004;Basim et al, 2005;Bencheikh-Latmani et al, 2005;Braz and Marques, 2005;Hu et al, 2005;Methe et al, 2005;Permina et al, 2006) and had higher transcript levels in sediment-grown cells (Table 7).…”
Section: Locus Idmentioning
confidence: 99%
“…Plasmid-borne genes for copper resistance in X. vesicatoria have similarities to the cop operon from P. syringae (43). Nevertheless, on the chromosome, the organization of the copper resistance genes appears to be uncommon, and occurrence of this type of resistance is rare in X. vesicatoria (3). The copper resistance genes described by Lee et al (22) in X. arboricola pv.…”
mentioning
confidence: 99%
“…Although most copper resistance genes characterized from plant-pathogenic bacteria have been shown to be plasmid borne (4,6,12,26,37,43), chromosomal copper resistance genes have also been identified (3,22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation